Suboptimal industry adherence to the design specifications of the mandatory pregnancy warning label - Asad Yusoff; Bella Sträuli; Alexandra Jones; Paula O’Brien; Jacquie Bowden; Michelle Jongenelis; Aimee Brownbill; Tim Stockwell; Simone Pettigrew (Australian and New Zealand Journal of Public Health)
Objective: To assess whether products sold in the Australian alcohol market are displaying the mandatory pregnancy warning label as per the design requirements. Methods: Between June and November 2023, data collectors photographed 5,964 unique alcoholic products from three Sydney alcohol retailers. A random sample of 20% of the 3,760 products displaying the mandatory pregnancy warning label was analysed to assess whether they met the design requirements outlined in the Food Standards Code. Results: Across the sample, 11% of products displaying the mandatory pregnancy label did not do so correctly. Adherence was lowest for spirits (73%), then wine (90%), beer (94%) and premix (97%). In terms of package type, adherence was lowest for individual beverages in containers >800 ml in volume (74%). Conclusions: The findings indicate that the application of the mandatory pregnancy warning label may be suboptimal in the Australian alcohol market. The lower adherence among spirits and wine products is concerning given their higher alcohol content. Implications for Public Health: For the effectiveness of the mandatory pregnancy warning label to be optimised, it must be displayed as per specifications. There is a need for ongoing compliance monitoring to improve adherence.